Meningkatkan Upaya Pelestarian Lingkungan Melalui Kegiatan Penghijauan Dengan Memanfaatkan Lahan Kosong - Feby Yolanda Feby; Maya Yuliana; Azura Luthfiyah; Rahmat Hidayat Hidayat; Neng Sholihat (Jurnal Pengabdian UntukMu NegeRI, 2022)
Conceptually, what is able to overcome problems regarding the environmental crisis is to carry out environmental conservation activities in the form of reforestation. The word preservation comes from the word "sustainable" which means to remain as it was before, not to change, to endure eternally. Meanwhile, preservation means the process, method, act of preserving, protecting from destruction and damage, preserving, conserving, managing natural resources that ensure their wise use and ensure the continuity of their supply while maintaining and improving the quality of their value and diversity. Environmental conservation is an effort to deal with problems that arise in an area. In this activity Kkn group 5, Group 5 held environmental conservation by applying the concept of reforestation by utilizing vacant land located on Jalan Kabun, Perum. Griya Firdaus Permai RT 01 / RW 08, Tampan District, Tuahmadani Village. This activity is a form of community service program.